Effects of Different Spectral Energy Distributions on Physiological Behavior and Hormone Levels in Depression - Chunyu YANG; Zhiyuan ZHANG; Juntao MA; Ting CHEN (Tehran University of Medical Sciences, 2018)
Background: The increasing worldwide incidence of depression causes massive economic losses to the country and society. Insufficient sun exposure aggravates depressive symptoms in patients with depression. Preventive light replenishment is provided to patients with depression and the potential population. In addition, we studied the applicable spectrum, which is crucial in the prevention of depression. Methods: Forty depressed male rats were randomly divided into five groups of 8 rats each: depressive model, microwave sulfur lamp, halogen lamp, fluorescent lamp, and LED lamp groups. Rats in the illuminated groups were exposed to light for 45 days for 2 h daily. Eight healthy rats were selected for the control group. The body weight and general behaviors of rats were recorded. After the experiment, peripheral blood was collected from the tail vein, and the concentrations of MT, 5-HT, NA, and BDNF in serum were detected by ELISA. Results: After the model was established, the body weight of rats in the depressive model group increased slowly. Compared with those of the control group, the results of the three behavioral tests were significantly different (P<0.05); the contents of MT, 5-HT, NA, and BDNF were relatively low (P<0.05). In addition, depression characteristics were significant. Rats regained their pleasant sensation after microwave sulfur lamp intervention. Compared with the rats in the depressive model group, the levels of MT, 5-HT, NA, and BDNF increased sharply. Conclusion: The spectral energy distribution of microwave sulfur lamp is similar to the solar spectrum, which can alleviate depressive symptoms in depressed rats.